MENYOAL IMPLEMENTASI TADRIJ DALAM UU PPSK (ANALISIS KEWAJIBAN SPIN-OFF LKS) - Abqory Najih, Rifqi (UNES Law Review, 2023)
This article discusses two main topics; first, about the removal of the maturity of the spin-off implementation for LKS in UU PPSK, and second, an analysis of the implementation of the tadarruj fi tathbiq ash-sharia method on the existence of the UUS based on expert opinions and its suitability with the spin-off policy. The conclusion in this article is; 1) the removal of the due date for the implementation of spin-off in UU PPSK revives the debate on the implementation of the tadarruj fi tathbiq ash-sharia method. Based on the arguments of experts, the method of tadarruj fi tathbiq ash-sharia can refer to the current condition (condition base) or refer to the time of expiration of the temporary law (timeline base). The timeline base is more appropriate as a benchmark for the implementation of tadarruj fi tathbiq ash-sharia because temporary laws should not be implemented continuously, maximum efforts need to be made for the creation of ideal laws. For this reason, The Financial Services Authority needs to regulate the maturity of the spin-off implementation in POJK so that the principles of tadrij are still implemented.